Printed and Laser-Scribed Stretchable Conductors on Thin Elastomers for Soft and Wearable Electronics - Keller, Kirill; Grafinger, David; Greco, Francesco (Frontiers in Materials, 2021)
As printed electronics is evolving towards applications in biosensing and wearables, the need of novel routes to fabricate flat, lightweight, stretchable conductors is increasing in importance. A suitable strategy for creating soft yet robust and stretchable interconnections in the aforementioned technological applications is to use print-related techniques to pattern conductors on top of elastomer substrates. In this study some thin elastomeric sheets – two forms of medical grade thermoplastic polyurethanes and a medical grade silicone – are considered as suitable substrates. Their mechanical, surface and moisture barrier properties -relevant for their application in soft and wearable electronics- are first investigated. VariousDFour different approaches are tested to pattern conductors, based on: screen printing of (i) conducting polymer (poly(3,4 ethylenedioxythiophene): polystyrene sulfonate, PEDOT:PSS), or (ii) stretchable Ag ink, and (iii) laser-scribing of Laser Induced Graphene (LIG). The electromechanical properties of these materials are thoroughly investigated by means of tensile testing and concurrent electrical measurements up to a maximum strain of 100%. Performance of the different stretchable conductors is compared and rationalized, evidencing the differences in onset and propagation of failure. Selected materials are then used in a proof of concept application as connectors for a wearable tattoo biosensor.